Exchange Rate Volatility and Export Performance: Case of Malaysia - Hakim, Amirul (International Journal of Economics, 2024)
Purpose: The aim of the study was to investigate the exchange rate volatility and export performance: case of Malaysia Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Exchange rate volatility negatively impacts Malaysia's exports, reducing both volumes and revenues. Stable exchange rates are crucial for export competitiveness and attracting foreign investment. Effective hedging and exchange rate policies are recommended to mitigate volatility's adverse effects. Macroeconomic stability and structural reforms are essential for Malaysia's resilience to external shocks. Managing exchange rate volatility is key for sustaining Malaysia's export-led growth and fostering economic development. Unique Contribution to Theory, Practice and Policy: Portfolio balance theory, j-curve theory & competitive devaluation theory may be used to anchor future studies on the exchange rate volatility and export performance: case of Malaysia. Malaysia can provide practical insights into how exporters can effectively integrate risk management strategies into their operations to mitigate the adverse effects of exchange rate volatility. Malaysia can serve as a model for proactive policy responses to exchange rate volatility, offering lessons and strategies that can be adapted by policymakers in other emerging economies.